Novel techniques and preliminary results of ex vivo liver resection and autotransplantation for end‐stage hepatic alveolar echinococcosis: A study of 31 cases. Issue 7 (21st January 2018) - Yang, Xianwei; Qiu, Yiwen; Huang, Bin; Wang, Wentao; Shen, Shu; Feng, Xi; Wei, Yonggang; Lei, Jianyong; Zhao, Jichun; Li, Bo; Wen, Tianfu; Yan, Lunan
Abstract : Ex vivo liver resection combined with autotransplantation is a recently introduced approach to cure end‐stage hepatic alveolar echinococcosis (HAE), which is considered unresectable by conventional radical resection due to echinococcal dissemination into the crucial intrahepatic conduits and adjacent structures. This article aims discuss the manipulation details and propose reasonable indications for this promising technique. All patients successfully underwent liver autotransplantation with no intraoperative mortality. The median weight of the autografts was 636 g (360‐1300 g), the median operation time was 12.5 hours (9.4‐19.5 hours), and the median anhepatic phase was 309 minutes (180‐ 460 minutes). Intraoperative blood loss averaged 1800 mL (1200‐6000 mL). Postoperative complications occurred in 13 patients during hospitalization; 5 patients experienced postoperative complications classified as Clavien‐Dindo grade III or higher, and 2 patients died of intraabdominal bleeding and acute cerebral hemorrhage, respectively. Twenty‐nine patients were followed for a median of 14.0 months (3‐42 months), and no HAE recurrence was detected. The technique requires neither an organ donor nor any postoperative immunosuppressant, and the success of the treatment relies on meticulous preoperative assessments and precise surgical manipulation. Abstract : This article discusses the details of ex vivo liver resection and autotransplantation in the treatment of end‐stage hepatic alveolar echinococcosis, including the feasibility, indications, preparation, technical innovations, and postoperative outcomes. See the video online atamjtransplant.com/videos .